Sensitive direct x-ray detectors based on the In–Ga–Zn–O/perovskite heterojunction phototransistor. (1st March 2022) - Cao, Yong; Ge, Yongshuai; Sha, Xin; Meng, Lingqiang; Gao, Yuanhong; Li, Bo; Yu, Xue-Feng; Li, Jia
Abstract: Direct x-ray detectors are essential in many applications including medical tomography, security inspection, nondestructive testing, crystallography and astronomy. Despite the rapid advances in recent years, the currently available direct x-ray detectors are still limited by the insufficient photon-to-charge conversion, compromising the detection sensitivity, ease of fabrication, cost and flexibility. Here we demonstrate a device concept of heterojunction phototransistor with high internal-gain effect to realize the sensitive x-ray direct detection. Specifically, the heterojunction phototransistors are mainly composed of an industrially available In–Ga–Zn–O channel and all-inorganic perovskite nanocrystals used as x-ray photoconductor. In contrast to the conventional diode-based x-ray detectors, phototransistor allows both electrical gating and photodoping effect for efficient carrier density modulation, leading to the low dark-current and high photoconductive gain. The introduction of such high-gain mechanism into x-ray detectors can offer internal signal amplification for photogenerated currents without the increment of noise, thereby leading to the high sensitivity over 10 6 μ C Gyair −1 cm −2 and detection limit down to 3 μ Gyair s −1 . These results suggest that the heterojunction x-ray phototransistor can provide the most promising platform to achieve high-performance direct x-ray detectors with both high sensitivity, light weight, flexibility and low cost.